2014
DOI: 10.2147/prom.s66737
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient satisfaction with the preoperative anesthetic evaluation

Abstract: BackgroundThe evaluation of patient satisfaction is a core aspect of the continuous quality improvement in anesthesia service that can be affected by the preoperative anesthetist visit. This visit enables the anesthetist to know about the patient’s general health status and the nature of surgery, to choose the type of anesthesia, and to discuss perioperative complications and their management with the patient. Patients have sometimes complained about the information given during the preoperative anesthetic eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
(7 reference statements)
4
13
0
Order By: Relevance
“…The overall satisfaction of the Rwandan patients was similar to this study (67.3%) while the Saudi Arabian patients were a little less satisfied (61.9%) [24, 25]. A study done in Ethiopia that focused only on preoperative period revealed an overall satisfaction level of 65% [26].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The overall satisfaction of the Rwandan patients was similar to this study (67.3%) while the Saudi Arabian patients were a little less satisfied (61.9%) [24, 25]. A study done in Ethiopia that focused only on preoperative period revealed an overall satisfaction level of 65% [26].…”
Section: Discussionsupporting
confidence: 71%
“…Lack of preoperative surgical information and guidance was also one of the causes of dissatisfaction according to the study done at Sohag University [25]. Moreover, in an Ethiopian study, only 32.4% of the patients received information about the type of anaesthesia and only 20.6% of the patients received information about possible postoperative complications [26]. Preoperative communication from anaesthetists outlining anaesthesia options and realistic postoperative expectations cannot only alleviate anxiety, but offers patients a sense of control over their care.…”
Section: Discussionmentioning
confidence: 99%
“…This is in-line with previous studies. [2243] In relation to this, ASA physical status is commonly used for stratification of perioperative outcomes. We found 71.3% PAETs had appropriate ASA physical status record.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of patient satisfaction after surgery and/or anesthesia has been increasingly recognized both in its own right and as a metric for quality of care. [53][54][55] Furthermore, there is some evidence linking positive patient experience and clinical outcome. [56][57][58] Concerns have arisen, however, over the use of non-validated tools to measure patient experience despite the availability of well-validated instruments.…”
Section: Patient-reported Experience Measures (Prems)mentioning
confidence: 99%